Electronic cigarette use among adolescents: a cross-sectional study in Hong Kong. (December 2016) - Jiang, Nan; Wang, Man; Ho, Sai; Leung, Lok; Lam, Tai
Abstract Background Little is known about electronic cigarette (e-cigarette) use among Chinese adolescents. We examined the prevalence of current (past 30-day) e-cigarette use and its associated factors in a large sample of adolescents in Hong Kong. Methods We analyzed data of the School-based Survey on Smoking among Students 2012/13 from a representative sample of 45, 857 secondary school students (mean age: 14.8 ± 1.9). We conducted chi-square tests andt -test to compare current e-cigarette use by covariates. We used multivariable logistic regression to examine the association between current e-cigarette use and demographic variables, parental smoking, peer smoking, knowledge about the harm of cigarette smoking, attitudes toward cigarette smoking, cigarette smoking status, use of other tobacco products, and alcohol consumption. Results Overall, 1.1 % of students reported current e-cigarette use. Of e-cigarette users, 11.7 % were never-cigarette smokers, 15.8 % were experimental cigarette smokers, 39.3 % were former cigarette smokers, and 33.2 % were current cigarette smokers. Current e-cigarette use was associated with male sex, poor knowledge about the harm of smoking, cigarette smoking, use of other tobacco products, and alcohol consumption. Conclusions Surveillance and intervention efforts should address a wide range of tobacco products, including e-cigarettes. Tobacco cessation programs should also address alcohol use collectively. Policies prohibiting e-cigarette sales to minors may help prevent e-cigarette uptake among adolescents.